THE PREVALENCE OF SCHIZPHRENIC PATIENTS WHO USED HEALTH SERVICE FACILITY: ANALYTICAL STUDY ON BPJS DATA SAMPLE 2015-2016 - Farrassafitri, Maitsa
Schizophrenia is a chronic and severe mental disorder that has a fairly heavy burden. The Indonesian Health Basic Research (Riset Kesehatan Dasar, Riskesdas) shows that the prevalence of schizophrenia in Indonesia in 2018 was 1.8 per mil population, slightly increased from the 2013 figure of 1.7 per mil population. This study aims to determine the prevalence of schizophrenia patients using National Health Insurance (Jaminan Kesehatan Nasional, JKN) as a third party payer in 2015-2016, its distribution frequency, and the influence of demographic factors such as gender, age, marital status, occupation status, and socioeconomic status on the severity of schizophrenia. This is descriptive observational study using secondary data of BPJS in the period of 2015-2016. Data sample was obtained by stratified random sampling method and has been de-identified to protect the patients’personal data. The data were analyzed using SPSS version 25.0. Univariate analysis was used to determine the frequency and percentage of data distribution and the bivariate for the assessment of significant relationship between demographic factors and the severity of schizophrenia. The results showed that the prevalence of schizophrenic patients using JKN as the third party payer in 2015-2016 period was 0.5 per mil. The majority of patients were male (64.7%), aged 25-34 years (29.4%), not married (37.9%), could not afford to pay dues or were totally disabled (52.4%), and occupy lower socioeconomic status. Significant associations (p<0.001) were observed between sex, age, marital status, occupation, as well as socioeconomic status and patient severity, as seen from length of stay and type of service.